Answer:
12 and -3
Explanation:
Let's assume the first number to be X And
The second number to be Y
First statement says that X - Y = 15_____ equation 1
And the second statement says that
1/3 × (X + Y) = (1/4 × X)
Open up the above bracket and expand the equation and we have
4x + 4y = 3x
X + 4Y = 0_______equation 2
From equation 1 which is x - y = 15,
Make X the subject of the formula and replace in equation 2
X = 15 + y
Replace the above in equation 2
(Which is X + 4Y = 0)
15 + y + 4y = 0
15 + 5y = 0
Y = -3
Now substitute Y = -3 in equation 1 above
X - Y = 15
X-(-3) = 15
X + 3 = 15
X = 12.
Both numbers are therefore, 12 and -3 respectively